2017
DOI: 10.17222/mit.2015.217
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion determination of reinforcement using the electrical resistance method

Abstract: The determination of reinforcement corrosion using the electrical resistance method of embedded bars in the concrete beams in laboratory conditions is described in this paper. For comparison, the achieved data from non-destructive measurements were compared to data from subsequent destructive tests when weight losses were recorded for each of the steel bars after their exposure time. Laboratory measurements of the reinforcements were realized particularly for verification of whether the electrical resistance m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…The available methods of reinforcement corrosion diagnostics for structures in use include electrochemical tests [38][39][40][41][42]. One such method is the semi-nondestructive method of measuring polarization resistance with the use of a galvanostatic pulse [43].…”
Section: Diagnostic Methods For Assessing the Degree Of Reinforcementmentioning
confidence: 99%
“…The available methods of reinforcement corrosion diagnostics for structures in use include electrochemical tests [38][39][40][41][42]. One such method is the semi-nondestructive method of measuring polarization resistance with the use of a galvanostatic pulse [43].…”
Section: Diagnostic Methods For Assessing the Degree Of Reinforcementmentioning
confidence: 99%
“…Specifically, the threshold expansion pressure and corrosion rate of concrete reaches the maximum at the moment of cover cracking, which has been widely studied by researchers [1,[6][7][8][9]. In the past thirty years, much effort focused on experimental studies has been directed towards the exploration of cover cracking time induced by the corrosion of reinforcing bars [10][11][12][13][14], along with a variety of corrosion models that were developed and implemented to predict concrete cover cracking time [15][16][17][18][19]. Precisely, among the above models, thick or thin-walled cylinder and elasticity theory are usually utilized for modeling the concrete with embedded steel bars and evaluating the cover cracking time, respectively [6,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, the current research agrees with the experimental results, which have shown that the bond loss of reinforced concrete due to corrosion is in line with the increase in surface cracking. In this framework, predictive models of bond loss have been introduced by different researchers [21,22,25,[34][35][36][37][38]. Apostolopoulos and Koulouris [21] proposed exponential predictive curves of bond loss in tandem with surface cracking width, by non-linear regression analysis, based on experimental results (Figure 9), by drawing attention to the influence of stirrups spacing.…”
Section: Resultsmentioning
confidence: 99%